Work-related stress among nurses working in northwest Amhara Referral Hospitals; a burden for hospitals - Enyew Getaneh Mekonen; Mignote Hailu Gebrie; Senetsehuf Melkamu Jemberie (Elsevier, 2022)
Introduction: Work-related stress in nursing practice leads to absenteeism, a high rate of error, and a drop in work performance resulting in lethal threats to patient safety. Research findings regarding work-related stress among nurses are very limited in northwest Ethiopia. Therefore, this study was conducted to determine the prevalence and associated factors of work-related stress among nurses working in Debre Markos and the University of Gondar referral hospitals, northwest Ethiopia. Methods: An institution-based cross-sectional study was conducted from 19th February to 20th March 2019. A simple random sampling technique was used to select 348 study participants. A structured pretested self-administered questionnaire was used to collect data. Descriptive statistics, bivariable and multivariable logistic regression analyses were carried out. The statistical association was declared using an AOR at a 95 % confidence interval and a P-value of < 0.05. Results: The prevalence of work-related stress among nurses was 29.2 %. Those nurses who had work-related fatigue [AOR = 2.35; 95 % CI (1.41, 3.91)], interruption during work [AOR = 1.83; 95 % CI (1.08, 3.10)], and commit an error [AOR = 1.89; 95 % CI (1.13, 3.16)] were at a higher risk of developing work-related stress. Conclusion: Greater than one-fourth of nurses had work-related stress. Factors like fatigue, interruption, and committing an error were significantly associated with work-related stress. It is better to reduce work-related fatigue, minimize work interruption, and reduce error occurrence by performing procedures in the right way to alleviate work-related stress.